Crosstalk between transposase subunits during cleavage of the mariner transposon - Claeys Bouuaert, Corentin; Walker, Neil; Liu, Danxu; Chalmers, Ronald (Oxford University Press, 2014)
Mariner transposition is a complex reaction that involves three recombination sites and six strand breaking and joining reactions. This requires precise spatial and temporal coordination between the different components to ensure a productive outcome and minimize genomic instability. We have investigated how the cleavage events are orchestrated within the mariner transpososome. We find that cleavage of the non-transferred strand is completed at both transposon ends before the transferred strand is cleaved at either end. By introducing transposon-end mutations that interfere with cleavage, but leave transpososome assembly unaffected, we demonstrate that a structural transition preceding transferred strand cleavage is coordinated between the two halves of the transpososome. Since mariner lacks the DNA hairpin intermediate, this transition probably reflects a reorganization of the transpososome to allow the access of different monomers onto the second pair of strands, or the relocation of the DNA within the same active site between two successive hydrolysis events. Communication between transposase subunits also provides a failsafe mechanism that restricts the generation of potentially deleterious double-strand breaks at isolated sites. Finally, we identify transposase mutants that reveal that the conserved WVPHEL motif provides a structural determinant of the coordination mechanism.